Online Learning Using PhET Simulation Videos and Real Laboratory Videos for Students' Understanding of the Hydrostatic Pressure Concept - I Komang Werdhiana; Kamaluddin Kamaluddin; Syamsuriwal Syamsuriwal; Ni Made Wiwik Astuti (Universitas Lambung Mangkurat, 2023)
This study aims to analyze the effect of the PhET simulation video (VSP) and real Laboarturium video (VLN) on high school student's understanding of the concept of hydrostatic pressure in online learning. The research was conducted in three representative schools in Palu City. This study used a pseudo-experimental method by comparing: 1) Experiment class 1 taught based on VSP-VLN design with Experiment class 2 taught based on VLN-VSP design; 2) Experiment class 1 and control class whose learning is based on conventional learning; and 3) experimental class 2 with control class. The determination of experimental classes and control classes in each school was carried out by purposive sampling. The statistical test results for the first case showed no significant difference between Experiment Class 1 and Experiment 2 (significance value greater than 0.05). Meanwhile, between Experiment Class 1 and the control class, there is a difference in the N-Gain value (%). This is supported by a significance value of less than 0.05. A comparison between the Experiment 2 class and the control class also shows differences. The average N-Gain (%) score of Experiment Class 1 and Experiment Class 2 is higher than the average value of the N-Gain (%) of the control class. This study concludes that learning using a combination of PhET simulation videos and real laboratory videos, in any order, can positively influence students' understanding of physics concepts compared to conventional learning in the entire online learning system. Video content can be used online or face-to-face to learn physics concepts directly through simulations and real laboratories.